2020
DOI: 10.1002/wene.393
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on carbon and metal based electrocatalysts for vanadium redox flow battery

Abstract: Attractive features of vanadium redox flow battery (VRFB) such as long durability, easy scalability, and low levelized cost of energy have influenced its prominence in the sectors where renewable energy is to be stored at a large scale. However, viability of VRFB to be used for a wide‐range of applications such as household electrification, electric vehicle charging infrastructure, and so on has been limited by its low power density. In principle, the power density of VRFB is dependent upon rate of electrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous studies have reported improved electrochemical activity by applying electrocatalysts in carbon materials. [15][16][17][18][19] Transition metal oxides have attracted signicant attention as electrocatalysts because of the variable oxidation state of a transition metal that facilitates the redox reaction and the oxygen vacancy, which increases the electrochemical activity as an active site. 20,21 Oxygen vacancies have been intentionally employed in transition metal oxides as active sites for several electrochemical reactions in the eld of defect engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported improved electrochemical activity by applying electrocatalysts in carbon materials. [15][16][17][18][19] Transition metal oxides have attracted signicant attention as electrocatalysts because of the variable oxidation state of a transition metal that facilitates the redox reaction and the oxygen vacancy, which increases the electrochemical activity as an active site. 20,21 Oxygen vacancies have been intentionally employed in transition metal oxides as active sites for several electrochemical reactions in the eld of defect engineering.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to mention here in passing, that the electrocatalytic effects in VRFB reactions is comparatively (to H 2 and O 2 electrocatalysis) weak, often poorly reproducible and time-dependent. [286][287][288][289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] We shall note also, that some of the aforementioned "quantum jumps" refer principally to academic innovations, as they have proven hard to scale-up and have not been universally-adopted by the flow-battery industry. 238 In conclusion of this section we shall ask ourselves the question: why do we want to increase the area-specific power of RFB stack ?…”
Section: Vanadium Rfbs-the Technology Frontrunnersmentioning
confidence: 99%
“…Improved hydrophilicity and higher active surface area is essential for attaining a uniform potential and current distribution on the surface of electrode and higher electrolyte utilization (Gautam et al, 2020). Whereas appropriate electrocatalysis of the redox reactions on the surface of electrode is essential for reducing the overpotential losses by enhancing the reaction kinetics (Liu et al, 2018; Singh et al, 2021). Several methods of pretreatment of bare GF at fundamental level have been explored and are still under exploration (Gautam & Verma, 2020; B. Li et al, 2013; Maleki et al, 2020; Mehboob et al, 2018; Wei et al, 2012).…”
Section: Materials Associated With Vrfb Systemmentioning
confidence: 99%
“…The adverse effects of production of electrical energy from conventional fossil fuels have influenced the prominence of renewable energy resources (Kwabi et al, 2020; Singh et al, 2021). However, it is well known that the renewable energy resources are intermittent in nature thus the sustainability in the current ecosystem is primarily dependent on the availability of technologically and commercially viable electrical energy conversion and storage technology (Winter & Brodd, 2004).…”
Section: Introductionmentioning
confidence: 99%